Recovery after stroke - Skilbeck, Clive E (1983)
One hundred and sixty-two patients were referred to a rehabilitation unit after an acute stroke. The patterns of recovery of overall functional ability, arm function, walking and speech in 92 of 101 survivors have been analysed. In all modalities the majority of recovery occurs within 3 months; although improvement is seen thereafter it does not reach statistical significance. Possible reasons for the apparent lack of late recovery are discussed.